Perkembangan Pemikiran Ulil Anshar Abdalla dari Islam Liberal ke Islam Spiritual 2001-2019 - Debby Citra Diarti (Qurthuba: The Journal of History and Islamic Civilization, 2019)
Abstract: The focus of the study in this article is about the transition of Ulil Abshar Abdallla's thought. This research answers the problem of how the figure of an Ulil and the history of liberal Islam and the entry of liberal Islamic thought in Indonesia, especially the formation of the liberal Islamic network from 2002 to 2019. In this study the authors use the historical method by using secondary sources derived from literature. The author also conducts interviews through social media. This approach is useful in revealing how Ulil's thinking develops and knowing the dynamics of his thinking. In terms of theory, the author uses the theory of archeology of knowledge put forward by Michel Foucault, explaining that a development and conflict in life cannot be separated from previous life. And to find out a development, you have to re-collect previous and recent problems. From the results of this study it can be seen that Ulil was a person born from an NU family. He has quite a unique mind and caused a very interesting controversy. When he wrote an article entitled "Refreshing Understanding of Islam". Not only that, Ulil himself is the coordinator of the Liberal Islam Network. An organization that voices the thoughts and ideas of young intellectuals freely to the public. Besides that, the dynamics of thought that Ulil has attracted quite a lot of attention, changing from liberal to spiritual thinking. Keywords: Ulil Abshar Abdalla, Liberal Islam, Spiritual Islam